Analysis of structured discharge planning implementation for discharged inpatients: a multicenter study - Candra Dewi Rahayu; Ika Purnamasari; Fifi Alviana; Dwi Ari Wibowo; Haeril Amir (PAGEPress Publications, 2024)
Discharge planning is an approach taken by the nurse, patient, and family that includes a needs assessment that will address a detailed care plan after the patient is discharged from the hospital. Discharge planning is essential for patients to prevent re-visiting patients with the same complaints or symptoms that require new treatment and to reduce length of stay for patients. In addition, a structured discharge planning can improve the quality of nursing care. This study aimed to analyze the implementation of structured discharge planning in inpatients. The method employed is a descriptive quantitative carried out in 9 hospitals. The results show that 78.03% of discharge planning has been carried out on inpatients. 54.3% of discharge planning was carried out since the patient's admission, and 45.7% was carried out when the patient was about to be discharged. Discharge planning is carried out ranging from assessment, diagnosis, intervention, implementation and evaluation. Discussion and conclusion state that the discharge planning has been carried out in a structured manner but the implementation has not been optimal and has not been fully performed when the patient is admitted to undergo treatment at the hospital.